Cultural values in sangihe ethnic song lyrics "masamper": an anthropological linguistic study - Lasut, Theresia Maria Conny; Marentek, Andriyani; Pamantung, Rina P.; Siamando, Tien (Linguistics and Culture Review, 2021)
This research focuses on traditional songs of ethnic community Sangihe Masamper that are usually performed in religion and or traditional ceremony, the problems discussed are what the expressions are used and what cultural meanings and values are included in those expressions. The objectives of this research are to describe: 1) the expressions, 2) the cultural meanings and values used in the songs of Masamper. The data are analyzed by using the theory of Koentjaraningrat (1979), Givon (2009) Fraenkel (1977), Kridalaksana ( 2008), and Pei and Gaynor (1980 ). The result of research are the expressions of the songs consist of Mawu, Ruata, Gengghona, Ghenggona, Langi, (God), anau sembau, Ku abe gagholokang’u u’waling liaghang gatinu, maning nahiu u pulangeng kai supato we senggesa-dedorongang mang sehimaneng kuhae ure mesasigesa, pirua, tembonang kawanua, Sangihe I kekendage, su pedarame and inang I amang. The cultural meanings are respect and honor to God, tight relationship, advice, work together, sympathy, respectfulness, admiration, togetherness, and honor. The cultural values are belief, brotherhood, education, unity, love, obedience, love homeland, and harmony. From the research, it can be concluded that the research needs to be carried out such as things that relate to sasasa (advice), more complete of Masamper.